Budaya Digital dan Transformasi Relasi Sosial: Telaah Kritis Pemikiran F. Budi Hardiman tentang Krisis Kehadiran di Era Digital - Felix Riondi Sugar; Anselmus K. Blikololong; Epi Pianus G. G. Wora; Fridolin De’e; Michael Savio M. K. Niron; Engelbertus Apryanto Aku; Evaldus Yogevalni; Oktavianus N. Dua (Khirani: Jurnal Pendidikan Anak Usia Dini, 2026)
The development of digital technology has brought about fundamental changes in patterns of communication and human social relations. Social media, as part of digital culture, not only serves as a means of information exchange but also shapes the ways in which people present themselves, interact, and interpret social reality. This article aims to analyze changes in social relations within digital culture through the perspective of F. Budi Hardiman’s philosophy of technology. This study employsa qualitative method with a literature review approach, focusing on Hardiman’s works as well as relevant literature on digital communication and media culture. The findings indicate that the digital revolution has shifted humanity from homo sapiens toward homo digitalis that is, humans whose existence is increasingly defined by activities within the digital realm. This condition gives rise to the phenomenon of telepresence, leading to a crisis of presence, a reduction in the depth of interpersonal relationships, and an increased potential for dehumanization in social interactions. Therefore, a critical attitude and ethical awareness are necessary so that humans remain subjects capable of controlling technology and maintaining the quality of social relationships amidst the development of digital culture.